The Unity of Psalm 19 - Kleven, James Terence (My University, 1981)
The unity of Psalm 19 has been questioned because of different content, form and divine names in two sections of the Psalm. The purpose of this thesis is to show that there is a conceptual unity to the Psalm. Each of the chapters responds to one of the three problems listed above.
The first chapter argues that the Psalm is unified by a theme of instruction. The heavens instruct men about the knowledge which the Creator possesses and which is displayed in the created order. The sun is a picture of the relevatory character of this knowledge. Through the use of carefully chosen terms in the latter part of the Psalm, the light imagery is shown to be present in law. The law of the Lord is also a source of instruction.
The second chapter argues that the parallelism of the Psalm is constructed in such a way as to focus the Psalm upon law. However, the parallelism itself cannot be used to suggest that the two sections of the Psalm are independent. This argument entails a criticism of several form-critical studies of the Psalm inasmuch as these studies have used the change in the type of parallelism in the Psalm as a factor which indicates that two independent forms are present in the Psalm.
The third chapter argues that the Psalm displays an assimilation of the idea of Creator into the idea of a Law-Giver. The most visible literary characteristic which shows the assimilation of these theological conceptions is found in the final colon of the Psalm. There are two epithets which summarise the two theological conceptions of the Psalm and their placement in apposition to the divine name YHWH draws together these conceptions in the deity YHWH.
Keywords: Religion; Religion